Influence of the hydration on autonomic modulation and cardiorespiratory parameters of coronary heart disease patients submitted to a cardiovascular rehabilitation session: crossover clinical trial protocol - Anne Kastelianne França da Silva; Maria Júlia Lopez Laurino; Laís Manata Vanzella; Lorena Altafin Santos; Felipe Ribeiro; Dayane Andrade Genoni Corazza; Luiz Carlos Marques Vanderlei (Universidade Estadual Paulista (UNESP), 2020)
Abstract Aims: The influence of fluid replacement, realized during and after the exercise on individuals with coronary artery disease (CAD) remains poorly understood. To investigate the influence of hydration on cardiac autonomic modulation, cardiorespiratory parameters and perceived exertion and discommodity, of coronary heart patients submitted to cardiac rehabilitation (CR) session. Methods: This cross-over clinical trial, will recruit 31 adults with more than 45 years old, participants of a cardiovascular rehabilitation program, with CAD diagnosis. The participants will be submitted to an experimental protocol composed of three phases: I) Maximal stress test; II) Control protocol (CP); and III) Hydration protocol (HP). The CP and HP will consist of 10 min of rest in a supine position, 15 min of warming, 40 min of treadmill exercise, 5 min of cooling down and 60 min of rest in a supine position. In the HP, the participants will be hydrated with mineral water, based on the bodyweight reduction of the CP. The water intake will be divided into eight equal portions, offered during the treadmill exercise and recovery period. On CP and HP will be evaluated linear and nonlinear indices of heart rate variability, the heart rate, systolic blood pressure, diastolic blood pressure, respiratory rate, oxygen partial saturation, perceived exertion and discommodity on specifics moments. Conclusion: The results of this study will allow us to identify if the proposed protocol will be able to positively influence the outcomes and, consequently, if could be implement in the clinical practice.